FACTORS AFFECTING EXCLUSIVE BREAST MILK TO MOTHERS HAVE 7-12 MONTHS BABIES IN THE WORK AREA OF SIDOMULYO PUBLIC HEALTH CENTER CENTRAL BENGKULU IN 2022 - lola vanianda, anisa; Dewi, Ratna; Savitri, Wewet (JURNAL KESEHATAN ALMUSLIM, 2023)
Exclusive breastfeeding is breastfeeding only for 6 months without additional food. Exclusive breastfeeding coverage in Bengkulu Province in 2021(67,8%), but the coverage of exclusive breastfeeding is still low at Sidomulyo (0,0%). Factors that influence exclusive breastfeeding are age,parity,and occupation. The purpose of the study was to determine the factors that influence exclusive breastfeeding.The research design used a cross-sectional approach to mothers of infants aged 7-12 months, totaling 38 samples with a purposive sampling technique. Data were analyzed by univariate, biavariate, and multivariate using chi-square statistical test and logistic regression.The results of univariate analysis of 38 mothers of infants aged 7-12 months mostly (76,3%) mothers did not gave exclusive breastfeeding, mothers aged 20-35 years, most (63,2%) mostly parity mothers (68,4),working mothers most (65,8%). The results of the bivariate analysis showed that there was a age (p=0,014 OR=1,60), parity (p=0.689 OR=1,84), occupation (p=0.000 OR=38,4), with exclusive breastfeeding. The influence factor is the work gave exclusive.The puskesmas is expected to carry out early detection of pregnant women who fail to provide exclusive breastfeeding and counseling on exclusive breastfeeding since pregnancy.